Resposta da avifauna a diferentes hábitats: investigando áreas nativas e em regeneração no Bioma Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The Pampa biome has a country physiognomy and has undergone increasingly intense conversion and fragmentation. In addition, it has few preservation areas which create a risk for endemic species and specialists, who suffer from the change of land use that transforms the heterogeneous environment into homogeneous that favors generalist species. In the Brazilian portion of the Pampa are about 480 species of the birds, of which about 50 are in some category of threat of extinction, many of these species depend on variation in height of vegetation, a characteristic that can be achieved with adequate livestock. In this context, the present study had as objective to describe how the different the habitat influence the patterns of richness and abundance of birds communities in wetlands, shrub field, regeneration field and riparian forest in the Pampa biome, extreme south of Brazil. For the sampling of the birds we used the technique of quantitative survey by (adapted) listening points, the sampling was carried out in four points of shrub, four of ciliary forest, four of fields in regeneration and three in humid areas. In order to analyze the patterns of wealth, we used the Rarefaction and Extrapolation Analysis. For abundance we used the Permutational Multivariate Analysis - Permanova, for the percentage of contribution of each species in the organization of the communities we used the Similarity Analysis - SIMPER. We recorded 127 species of 45 families for the total area. Of these 101 were recorded in the sampled environments. Two of the registered species are of interest for conservation: Cyanocorax caeruleus and Amazona pretrei. The native environments presented greater diversity and presented no significant difference between them when compared to fields in regeneration. We observed that the effects of changes in land use even after four years of regeneration are still visible in the composition of the bird communities, generating a lower richness pattern with increased abundance for the species that can take advantage of this more homogenous and modified environment.
Keywords: Campos Sulinos; Degradação Ambiental; Campos Sulinos; Ambiental degradation; CNPQ::CIENCIAS BIOLOGICAS